2021
DOI: 10.1186/s12995-021-00312-4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Disease Occupational Biomonitoring Collaborative Project (ROBoCoP): A longitudinal pilot study and implementation research in the Parisian transport company

Abstract: The ROBoCoP project is launched within the EU COST Action CA16113 “CliniMARK” aiming to increase the number of clinically validated biomarkers and focused on chronic obstructive pulmonary disease (COPD) biomarker development and validation. ROBoCoP encompasses two consecutive studies consisting of a pilot study followed by a field study. The pilot study is a longitudinal exposure assessment and biomarker study aiming at: 1-understanding the suitability of the candidate biomarkers in surveying populations at ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Furthermore, we found that OPEA is stable with respect to individual characteristics such as sex and age, but also with respect to some exposures such as tobacco smoking or different types of diets. Such a stability was also observed in the pilot clinical study [ 6 ] and in two ongoing studies [ 26 , 27 ], and is a valuable characteristic for a candidate biomarker, facilitating its interpretation and therefore its use in clinical practice.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, we found that OPEA is stable with respect to individual characteristics such as sex and age, but also with respect to some exposures such as tobacco smoking or different types of diets. Such a stability was also observed in the pilot clinical study [ 6 ] and in two ongoing studies [ 26 , 27 ], and is a valuable characteristic for a candidate biomarker, facilitating its interpretation and therefore its use in clinical practice.…”
Section: Discussionmentioning
confidence: 55%
“…Consequently, we could not investigate the effect of ethnicity on OPEA in this study sample. Nevertheless, the results from the French–Swiss study of subway workers [ 26 , 35 ] and those from the European cohort of nanotechnology workers [ 27 ] showed that OPEA did not differ across ethnicity groups. The tests were not statistically significant, with p = 0.158, and p = 0.776, respectively (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Security guards were responsible for maintaining order at the various stations, as well as on board of the metro, trains, bus and tram lines they use to travel around the network. Field measurements were collected over 6 weeks between 7th of October to 15th of November 2019 according to a registered research protocol (Canu et al 2021b ). All workers provided informed written consent prior to enrolment and completed an epidemiological questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…We expect subway workers to have greater PM exposures than subway commuters, and consequently, a greater chance of detecting possible biological responses. The obtained results should help in defining the most relevant biomarkers to measure in a large epidemiological study (Canu et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the suitability of the validated method, we used 164 EBC samples collected in an ongoing occupational field study [ 32 ]. This study included nine non-smoking healthy adults of both sexes working in the underground subway in Paris.…”
Section: Methodsmentioning
confidence: 99%